Southeast Asia in the new international era - Dayley, Robert (Routledge, 2020)
This newly revised eighth edition of Southeast Asia in the New International Era provides readers with contemporary coverage of a vibrant region home to more than 650 million people, vast cultural diversity, and dynamic globalized markets.